1990
DOI: 10.1055/s-2007-1004937
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triiodothyronine and Thyroxine on Mitochondrial α-Glycerophosphate Dehydrogenase Activity and Mitochondrial Protein Content of Liver, Muscle and Brain of Toad,Bufo melanostictus

Abstract: The responsiveness of the adult toad to triiodothyronine (T3) and thyroxine (T4) was studied by measuring the mitochondrial alpha-glycerophosphate dehydrogenase activity and mitochondrial protein content of liver, muscle and brain of toad. Both T3 and T4 increased the alpha-GPD activity and mitochondrial protein content of liver and muscle of toad. The extent of increase in the alpha-GPD activity and mitochondrial protein content were more pronounced with T3 than with T4. Further that the muscle exhibited more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Thyroid hormones especially induce a considerable increase in GPDH activity in the liver [3 ± 5]. As in mammals, toad liver showed GPDH responsiveness to both thyroxine (T 4 ) and triiodothyronine (T 3 ) [6]. Lee and Lardy [3] showed that feeding 2 % desiccated thyroid gland mixed with laboratory chow for 10 days in-creased the activity of rat liver GPDH by up to twenty times control values.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormones especially induce a considerable increase in GPDH activity in the liver [3 ± 5]. As in mammals, toad liver showed GPDH responsiveness to both thyroxine (T 4 ) and triiodothyronine (T 3 ) [6]. Lee and Lardy [3] showed that feeding 2 % desiccated thyroid gland mixed with laboratory chow for 10 days in-creased the activity of rat liver GPDH by up to twenty times control values.…”
Section: Introductionmentioning
confidence: 99%